Tanzania Social Accounting Matrix (SAM), 2009 - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
The Tanzania Social Accounting Matrix (SAM) for the year 2009 is a detailed representation of Tanzania's economy. It separates 58 activities and commodities; labor by different levels of education levels; and households by rural/urban areas as well as expenditure quintiles. Labor and household information are drawn from the most recent Tanzania Household Budget Survey. Finally, the SAM identifies government, investment, and foreign accounts. It is, therefore, an ideal tool for economywide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.